MANAJEMEN KURIKULUM, PEMBELAJARAN DAN KESISWAAN PENDIDIKAN DASAR - Chinyawaty, Chinyawaty; Suyono, Suyono; Sukma Indra Dewi, Radeni (CV. Lafadz Jaya, 2024)
This study aims to explore the implementation of curriculum management, teaching, and student affairs in primary education and their impact on school quality improvement. The research problem focuses on how these three aspects are effectively managed to support optimal educational processes. This study employed a qualitative method with a case study approach in a public primary school. Data were collected through interviews, observations, and document analysis to understand the strategies and challenges encountered in the implementation. The findings reveal that flexible curriculum management, innovation-based teaching, and a holistic approach to student management can enhance the effectiveness of the education process. The study concludes that the integration of curriculum management, teaching, and student affairs is crucial as strategic elements in creating a high-quality and sustainable educational environment.